Comparative transcriptomic analysis for identification of candidate sex-related genes and pathways in Crimson seabream (Parargyrops edita) - Binbin Shan (Nature Portfolio, 2021)
Abstract Teleost fishes display the largest array of sex-determining systems among animals, resulting in various reproductive strategies. Research on sex-related genes in teleosts will broaden our understanding of the process, and provide important insight into the plasticity of the sex determination process in vertebrates in general. Crimson seabream (Parargyrops edita Tanaka, 1916) is one of the most valuable and abundant fish resources throughout Asia. However, little genomic information on P. edita is available. In the present study, the transcriptomes of male and female P. edita were sequenced with RNA-seq technology. A total of 388,683,472 reads were generated from the libraries. After filtering and assembling, a total of 79,775 non redundant unigenes were obtained with an N50 of 2,921 bp. The unigenes were annotated with multiple public databases, including NT (53,556, 67.13%), NR (54,092, 67.81%), Swiss-Prot (45,265, 56.74%), KOG (41,274, 51.74%), KEGG (46,302, 58.04%), and GO (11,056, 13.86%) databases. Comparison of the unigenes of different sexes of P. edita revealed that 11,676 unigenes (9,335 in females, 2,341 in males) were differentially expressed between males and females. Of these, 5,463 were specifically expressed in females, and 1,134 were specifically expressed in males. In addition, the expression levels of ten unigenes were confirmed to validate the transcriptomic data by qRT-PCR. Moreover, 34,473 simple sequence repeats (SSRs) were identified in SSR-containing sequences, and 50 loci were randomly selected for primer development. Of these, 36 loci were successfully amplified, and 19 loci were polymorphic. Finally, our comparative analysis identified many sex-related genes (zps, amh, gsdf, sox4, cyp19a, etc.) and pathways (MAPK signaling pathway, p53 signaling pathway, etc.) of P. edita. This informative transcriptomic analysis provides valuable data to increase genomic resources of P. edita. The results will be useful for clarifying the molecular mechanism of sex determination and for future functional analyses of sex-associated genes.